Learning English in a Non-supportive Environment among Malay Learners in Secondary Schools - Ismail, Jamali (Universiti Putra Malaysia Press, 1994)
This study investigated the degree of exposure to English as a second language amongst Malay learners and the strength of the relationship between exposure to English amongst the learners and their competence in the language. It was assumed that the higher the degree of exposure to English the learners received, the more competent they were in the language. The sample of the study consisted of 44 I Form Four Malay learners from selected schools in Selangor. For the collection of data, a questionnaire was used to gather information relating to the learners' achievement in the SRP English Language paper and to measure the degree of their exposure to English. The analysis of data was carded out by using the cross tabulation and correlation procedures. The study showed that the learners, who were generally weak in English, received a minimal amount of exposure to the language. There was also indication of the presence of a significant relationship between exposure to English and competence in the language. The learning environment for English in Malaysia which is generally nonsupportive is also discussed and possible teaching strategies to overcome the learning problem are suggested.